Development of 3D interconnected nanoporous TiZrHfNbTaNi high-entropy alloy via liquid metal dealloying and subsequent synthesis of (TiZrHfNbTaNi)O high-entropy oxide - Jae Hyuk Lee; Soo Vin Ha; Jihye Seong; Akira Takeuchi; Ruirui Song; Hidemi Kato; Soo-Hyun Joo (Journal of Materials Research and Technology)
In this study, the liquid metal dealloying (LMD) process was employed to develop 3D interconnected nanoporous (3DNP) high-entropy alloys (HEAs) and high-entropy oxides (HEOs). Selective dissolution of Ni occurred in a molten Mg bath from a (TiZrHfNbTa)20Ni80 precursor alloy, while the immiscible elements Ti, Zr, Hf, Nb, and Ta self-organized into 3D interconnected structures. The initial precursor consisted of three distinct phases, which underwent sequential, stepwise selective dissolution due to variations in their phase stabilities at the reaction front. However, after a short processing time of 10 min, the synthesized 3DNP HEAs exhibited homogeneous elemental distributions, facilitated by rapid interfacial diffusion during thermal coarsening. The miscible Ni atoms in the precursor alloy demonstrated exceptional stability in the Mg melt, which contributed to a progressively slow dissolution phenomenon. As a result, the 3D interconnected ligaments retained their ordered orthorhombic crystal structure throughout the process. After 60 min, the Ni concentration decreased to 43.1 at.% and Nb- and Ta-enriched nanoprecipitates were uniformly formed, resulting in the development of a bimodal 3DNP structure. These crystal structure transformations closely matched the equilibrium crystal structures predicted by Thermo-Calc. The synthesized 3DNP HEA was oxidation heat treated at 1200 °C in dry air, producing 3DNP HEOs that retained the 3D interconnected structures. This study demonstrates the potential of the LMD process for fabricating advanced 3DNP materials with tunable compositions and microstructures for various applications.